Strategi Pengembangan Wisata Penangkaran Rusa Tahura Wan Abdul Rachman Kemiling Bandar Lampung - Lioralael, Anatasia; Zulfa Emalia (E-journal Field of Economics, Business and Entrepreneurship (EFEBE), 2025)
Conservation-based tourism plays a crucial role in balancing ecological sustainability and local economic benefits. The Deer Breeding Tourism at Tahura Wan Abdul Rachman, Kemiling, Bandar Lampung, holds significant potential for development to attract more visitors and support wildlife conservation. However, this area faces several challenges, including declining visitor numbers, limited facilities, and insufficient promotion. This study aims to formulate a development strategy for the deer breeding tourism site using the Analytical Hierarchy Process (AHP). The results indicate that animal welfare and health hold the highest priority (0.436), followed by promotion and marketing (0.283), visitor management and services (0.157), and infrastructure (0.124). The recommended strategies include improving wildlife care, optimizing digital marketing, enhancing visitor services, and upgrading supporting facilities. With the right strategy, this deer breeding tourism initiative is expected to contribute to environmental conservation while also boosting economic benefits for the local community.